ANALYSIS OF CHANGES IN THE COEFFICIENTS OF TRAFFIC VEHICLES INTENSITY INCREMENT IN TIME FOR THE MOTOR ROADS OF UKRAINE - Гамеляк, Игорь; Райковский, Виталий (SWorldJournal, 2021)
The paper presents an analysis of changes in coefficients of traffic vehicles intensity increment for eight major groups of vehicles (cars, light trucks, medium trucks, heavy trucks, medium buses, heavy buses, trucks with trailers and semi-trailers), whi